Implementation of Islamic Religious Education and Character Building Learning Based on the 2013 Curriculum in Elementary Schools - Nur Zahiyah; Parmujianto; A. Badaruddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to see how Islamic religious education and ethics are implemented in one of the state primary schools in Bantul area, Yogyakarta, based on the 2013 curriculum. This study used a qualitative method. The data used in this study came from interviews with PAI teachers and observing teacher and student learning activities in one of the 3rd grade elementary schools in Bantul district. This study shows that PAI teachers have prepared all learning tools needed for learning, including making lesson plans, syllabus, prota, prosem, and teaching strategies. Learning can be done in various ways, such as lecture, question and answer, presentation, discussion, practice, and project-based learning. However, these methods are less effective because there are still students who lack confidence and enthusiasm for learning. The evaluation stage applied by PAI teachers assesses three domains, namely, cognitive (knowledge), affective (attitude), and psychomotor (skills). As for inhibiting factors, teachers try to maximize the supporting factors that are already available at school in terms of improving the quality of learning.